Metabolic Bone Superscan in Carcinoma Breast with Occult Graves' Disease: Looking Beyond Skeletal Metastases - Parihar, Ashwin Singh (Indian J Nucl Med, 2018)
Extrathyroidal manifestations of autoimmune thyroid disorders include thyroid-associated ophthalmopathy, thyroid dermopathy, and thyroid acropachy. Thyroid acropachy is an extreme manifestation of autoimmune thyroid disorder characterized by clubbing and swelling of fingers and toes, with or without periosteal reaction of the distal bones. We present a 50-year-old woman, posttreatment for carcinoma breast (6 years back) and referred for bone scan for generalized body ache. Bone scan findings resulting in detailed clinical evaluation prompted toward the suspicion of a thyroidal disease with ultimate diagnosis of Graves' disease.